PEMALSUAN IDENTITAS SEBAGAI ALASAN PEMBATALAN PERKAWINAN (Analisis Putusan Pengadilan Agama Medan Nomor: 335/Pdt.G/2013/PA Mdn) - bagus ramadi (TAQNIN: Jurnal Syariah dan Hukum, 2020)
Falsification of identity is part of the marriage registration issue that must be resolved immediately. The obligation to register marriages by some people turns out to be a difficult issue to adhere to, especially for couples who have been married. Case Number: 335 / Pdt.G / 2013 / PA. Mdn is one of the problems in the Medan Religious Court because it changes the marital status from widower to single and widowed to girl and does not match the actual marriage guardian with the marriage guardian in the marriage record. This study analyzes the decision of the Medan Religious Court Number: 335 / Pdt.G / 2013 / PA. Mdn, to see the legal considerations of the judge who decided to cancel the marriage of the Defendants. From the results of the analysis, the authors found discrepancies and discrepancies in the legal basis used by judges to decide this case. The judge considered the falsification of identity as part of the non-fulfillment of the requirements and the harmony of the marriage so the marriage had to be canceled. However, for the author of counterfeiting status and guardian of marriage part of administrative errors that can be updated or recorded again. Keywords: Identification of Falsehood, Marriage Cancellation, Decision